RESPONS PELAKU UMKM ATAS PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 - Fersiani, Ekawati; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the respond of the business practitioners of micro, small, and medium enterprises (UMKM) on the calculation of rates and the basis of tax calculation, the easiness and the simplification of the payment of tax and the purpose of the issuance of Government Regulation No. 46 of 2013. The data has been obtained directly from 7 business practitioners of micro, small, and medium enterprises in Surabaya city as informants. The data collection has been done by conducting Interpretation Analysis Method. The result of the research shows that 1) In general, the business practitioners of micro, small, and medium enterprises (UMKM) agree on the change of rates and the basis of tax calculation; 2) the business practitioners of micro, small, and medium enterprises (UMKM) agree that the Government Regulation No. 46 of 2013 provide the easiness and the simplification of the calculation in the payment of tax; 3) the business practitioners of micro, small, and medium enterprises (UMKM) have an opinion that the purpose of the Government Regulation No. 46 of 2013 has not completely educated the public to be orderly and transparent administration in paying taxKeywords: Respond, Government Regulation No. 46 of 2013, Micro, Small, and Medium Enterprises (UMKM).